An Analysis of the Role of the National Social Security Fund Act Towards the Attainment of Social Security in Uganda - Derrick John Orishaba (Uganda Christian University, 2024)
Social security plays a vital role in promoting economic stability, reducing poverty, and ensuring the well-being of citizens, particularly in developing countries like Uganda. This research explores the effectiveness of the National Social Security Fund (NSSF) Act in enhancing social security in Uganda. The study adopts a mixed-methods approach, incorporating qualitative and quantitative techniques to analyze the legal, institutional, and socio-economic dimensions of social security provision under the NSSF Act. Drawing on an extensive literature review and empirical data collection, including interviews, surveys, and document analysis, the research examines the coverage, accessibility, adequacy, efficiency, and effectiveness of social security provisions under the NSSF Act. Additionally, the study investigates the socio-economic, cultural, and institutional factors that influence the implementation and outcomes of the NSSF Act, as well as the challenges and opportunities for reform. The findings of this research are expected to provide valuable insights for policymakers, practitioners, and stakeholders in the social security sector, informing evidence-based policy formulation, program design, and advocacy efforts aimed at strengthening social protection systems in Uganda. Ultimately, this research contributes to the broader discourse on social security enhancement and socio-economic development in Uganda and other similar contexts.
Undergraduate Research